Consumer Pre-Purchase Behavior in Indonesian Digital Commerce - Isma Azis Riu (Malaqbi Publisher, 2026)
The rapid expansion of digital commerce platforms in Indonesia has fundamentally reshaped how consumers engage with the pre-purchase phase of their decision-making journey. While scholarly attention has gravitated predominantly toward post-purchase outcomes, satisfaction, loyalty, and return behavior, the lived cognitive and evaluative experiences of consumers before purchase commitment remain comparatively underexplored, particularly in Southeast Asian market contexts. This study employs a qualitative research design, drawing on semi-structured in-depth interviews with twenty-four purposively selected digital commerce users across five major Indonesian cities, to illuminate the meaning-making processes, heuristic strategies, and credibility evaluation behaviors that characterize consumer engagement with price comparison tools and online review platforms. Guided by consumer decision-making theory, information processing theory, and the elaboration likelihood model, the analysis generates four overarching themes: (1) multi-platform search as a reflexive navigational practice; (2) price comparison tool usage as cognitive load management; (3) online reviews as primary trust anchors; and (4) fake review detection as a form of consumer digital literacy. These findings offer nuanced theoretical contributions to the pre-purchase behavioral literature and carry substantive implications for digital platform design and electronic word-of-mouth strategy in emerging markets.